Application tools technology in public administration (2016)
With the changes that overwhelm the world , public administration must incur a to transformation according to the new technologies that intrude as a means of agility , convenience and great savings and greater transparency index , according to their need to be side of innovation, transformation and upgrading of public policy , it is worth noting as technology trends generate changes within the state seeking to meet the needs of it and contribute to the development of the country.